ORIENTASI PENELITIAN PERTANIAN: MEMENUHI KEBUTUHAN PANGAN DALAM ERA GLOBALISASI - ANTARA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 1, No. 1 Februari 2001)
Since long ago Indonesia to face the food problem, even in the future will be a more serious problem if agriculture sector as food producer not were work on seriously. Since decrease emphasize toward agriculture sector, in floods of import rice enter the domestic market so that to decrease farmer’s desire planting the rice, rely on sources of food on rice only, and food diversification still limit of slogan or rhetoric entirely, has caused the national food security system more and more become weak. It’s appeared trade-off between the goal of food security and the income growth of farmers, so in the framework of meet the national food can be met in a policy strategy of selfsufficiency on trend. Its mean, to export when the national rice production surplus and to import when national rice production deficit, cause the absolute self-sufficiency cannot defended. To increase the household and national food security that faced on reduction the depending on import food and depending on one kind source of food namely rice, so food diversification must be back encouraged that followed by research and development, action program, and it’s to be as a national movement. Research of agriculture to meet the need of national food in globalization era, mainly food of non-rice carbohydrate in order to agribusiness orientation. Its mean, the research on every subsystem of non-rice food agribusiness system, to aim increase the food production, producer income, and value added of food product mentioned, so that more and more competitive in domestic and national market.
Keywords: National Food Security, Self-Sufficiency on Trend, Food Security, and Orientation of Agribusiness.